A Framework to Protect Unique Cultural Product using Blockchain Technology - Muhammad Hassif Imran, Muhammad Harris Irwan (Universiti Malaysia Sarawak (UNIMAS), 2019)
Songket market in Sarawak have been established since 1970, making it one of the longest existing market product. Songket perseverance is essential to ensure the originality of the artwork in the community. An effort can be done by encouraging the community to report pirated pattern. However, the method available does not lessen the case of pirated pattern in the songket market. Songket in Sarawak are mainly copied by other irresponsible people. By creating a new system that can detect the ownership of the songket pattern, this will increase the value of the songket pattern. The proposed system is to help the creator of the songket to preserve their songket pattern. Method used to develop the system are waterfall model to make it easy to develop the system. By using this methodology, tools and technologies like Ethereum Studio and Solidity programming language are used. The main objective is to preserve the authenticity of the produced songket. A system that can prevent the pirated songket from being sell in the market are achieved. Things that motivate me to develop this system are the producer of songket who can’t sell their songket properly since there’s counterfeit songket product in the market.